2019
DOI: 10.17478/jegys.618245
|View full text |Cite
|
Sign up to set email alerts
|

Student Perception on Teaching Materials Development to Increase Students’ Knowledge of Aceh's Maritime Potential

Abstract: Aceh has the potential as a world trade route, fish catch lane and marine tourism in Indonesia. Therefore, students' knowledge of Aceh's maritime potential needs to be developed. The purpose of this study was to determine student perceptions of teaching materials to Increase Students' Knowledge of Aceh's Maritime Potential. This study used quantitative research design. The results of the study were obtained from the answers to the questionnaires that were developed, validated, and tested by researchers. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 18 publications
(14 reference statements)
0
8
0
Order By: Relevance
“…Geography lessons at the high school level are able to provide learning experiences to students related to disaster countermeasures (Healey & Jenkins, 2000). This is also evident from previous studies that support the role of geography education in disaster education including: the use of local wisdom (Immaniar et al, 2019;Maryani & Yani, 2014), development of learning models (Maryani, 2010), and development of learning tools (Student activity sheets, modules, hand-outs, geography textbooks) (Akbar & Hartono, 2017;Iryanthony, 2015;Ridha et al, 2019;Ridhwan et al, 2019;Widyaningsih, 2014). Preparing students in facing disasters should be supported by curriculums that contain disaster education.…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…Geography lessons at the high school level are able to provide learning experiences to students related to disaster countermeasures (Healey & Jenkins, 2000). This is also evident from previous studies that support the role of geography education in disaster education including: the use of local wisdom (Immaniar et al, 2019;Maryani & Yani, 2014), development of learning models (Maryani, 2010), and development of learning tools (Student activity sheets, modules, hand-outs, geography textbooks) (Akbar & Hartono, 2017;Iryanthony, 2015;Ridha et al, 2019;Ridhwan et al, 2019;Widyaningsih, 2014). Preparing students in facing disasters should be supported by curriculums that contain disaster education.…”
Section: Introductionmentioning
confidence: 66%
“…This activity can also teach students to solve problems in their environment (Aliman et al, 2019). Resolving these environmental problems is a human responsibility in reducing the potential for disasters (Ridhwan et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned by Bustami, Syafruddin, and Afriani [28], the development of learning media such as student worksheets should address local potentials and issues, and the development of textbooks should be based on local wisdom [69]. Similarly, Ridhwan, et al [43] reported that the development of teaching materials could be derived from local potentials. Besides, the survey results also showed that Lake Tempe could be used as a learning resource.…”
Section: The Relevance Of Lake Tempe's Potential As a Learning Resourcementioning
confidence: 99%
“…However, the lake's potential should be aligned with the learning outcomes that students should achieve at all education levels. According to previous research [43], the utilization of local potential can enhance learners' comprehension of facts and process skills through direct observations. According to previous research [70], direct observation activities can provide students with experiences and understand phenomena based on facts.…”
Section: The Pre-service Biology Teachers' Responses Towards Lake Tempe's Potential As a Learning Resourcementioning
confidence: 99%
See 1 more Smart Citation